PENGARUH LATIHAN MENYERANG DAN MEMPERTAHANKAN GAWANG TERHADAP KETERAMPILAN MENGGIRING BOLA PADA PEMAIN SEPAKBOLA SSB UR PEKANBARU - Mahadir Effendi Effendi; Saripin '; Kristi Agust Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research was conducted to know whether there are effects of the attack exercise and defend the wicket against the dribble skills of the football game so that when doing the dribble get maximum results.This research used experimental research, with a population of football club athletes in SSB UR Pekanbaru, in this research, all population of the data 24 people. The instrument of this research used dribble test, which aims to measure the skills in dribble. After that, the data had been processed using statistics, to test normality was used the lilifors test at a significant level 0,05α. The hypotheses there are effects of the attack exercise and defend the wicket against the dribble skills. Based on the analysis of t-test was Tmean 7, 57 and Ttable 1,764, it means that Tmean>Ttable. Based on the analysis of data statistic, there is the average of pre-test was 19, 80 and the average of post-test was 19, 48, the data was normal. Based on the result of the data, it can be concluded that there was effects of the attack exercise and defend the wicket against the dribble skills on the football players in SSB UR Pekanbaru. Keywords: attack and defend the wicket, the dribble skills